2010
DOI: 10.1111/j.1745-4549.2009.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Sous Vide Cook-Chill Preserved Food at Different Shelf Life

Abstract: The effect of three different periods of storage life (0, 15 and 30 days) on the microbiological quality of several foods elaborated with the sous vide cook–chill procedure in a restaurant was studied. These foods are grouped in three categories: meat (breast chicken, foie gras, pork loin and entrecote of veal), fish (codfish, gilt head sea bream, hake and salmon) and vegetable (broccoli, courgette, potato and carrot). Total plate counts in the products studied were in the range of <1.00–3.74 log10 cfu/g. Coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
0
19
0
4
Order By: Relevance
“…Reductions in mesophilic and psychotrophic bacteria counts in sous vide fish of up to 3 log CFU g -1 in relation to the raw material have been reported by Shakila et al (2009) andCan (2011). The pH values were found to be within the limits established by the Regulation of Industrial and Sanitary Inspection of Animal Products (RIISPOA -Regulamento de Inspeção Industrial e Sanitária de Produtos de Origem Animal) (BRASIL, 1952), for external (<6.8) and internal (<6.5) fish meat, and they differed significantly between the fillets and the sous vide (Table 2).…”
Section: In Salmon Sous Vidementioning
confidence: 77%
See 2 more Smart Citations
“…Reductions in mesophilic and psychotrophic bacteria counts in sous vide fish of up to 3 log CFU g -1 in relation to the raw material have been reported by Shakila et al (2009) andCan (2011). The pH values were found to be within the limits established by the Regulation of Industrial and Sanitary Inspection of Animal Products (RIISPOA -Regulamento de Inspeção Industrial e Sanitária de Produtos de Origem Animal) (BRASIL, 1952), for external (<6.8) and internal (<6.5) fish meat, and they differed significantly between the fillets and the sous vide (Table 2).…”
Section: In Salmon Sous Vidementioning
confidence: 77%
“…This product has better color, flavor, texture and nutrient-retention characteristics compared with traditional cooking processes, representing an interesting alternative for consumption. Many studies have indicated the viability of using the sous vide process with different types of meat and fish (GALIMPIN-JOHAN et al, 2007;SHAKILA et al, 2009;MOL et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case of the study of the packaging technology in the cooked meat product Morcela de arroz (Pereira et al, 2015), the storage temperature for charcoal-broiled fish (Merivirta et al, 2003), brine salted versus unsalted cheese (Mucchetti et al, 2008) and the sous vide cooking of meat, fish and produce based products (Sebastia et al, 2010). In some cases the pathogen was not detected in any analysed sample.…”
Section: Figure 15mentioning
confidence: 99%
“…The 66.6% of them had been verified by external auditors. It is reported by Sebastia et al . (2010) that a developed and implemented traceability system is relevant to achieve food safety.…”
Section: Resultsmentioning
confidence: 53%